The need for a comprehensive and integrated approach to lung cancer policy in Europe. (November 2022) - Racovita, Monica; Wheeler, Eleanor; Wait, Suzanne; Albreht, Tit; Baird, Anne-Marie; Jassem, Jacek; McNamara, Aoife; Novello, Silvia; Radu-Loghin, Cornel; van Meerbeeck, Jan P.
Abstract: Lung cancer is the leading cause of cancer-related deaths in Europe. Europe's Beating Cancer Plan calls for a comprehensive approach to the disease in general but not specifically to lung cancer. Such a comprehensive approach, integrating efforts to strengthen anti-tobacco policies, early detection and underlying models of care, is sorely needed for lung cancer – particularly considering disruptions to care during the COVID-19 pandemic. In a recently published think piece, a multidisciplinary group of experts proposed four key policy priority areas. First, to reduce stigma and improve awareness of potential symptoms, there is a need to foster a better understanding of lung cancer – among the public and healthcare professionals. Second, opportunities for early detection should be enhanced, and the implementation of targeted screening through low-dose computed tomography should be encouraged as a complement to smoking cessation services. This complementarity should be recognised and built into joint policy proposals, with development and better integration of screening and smoking cessation programmes on the ground. Third, the socioeconomic inequalities underpinning disparities in outcomes in people with lung cancer must be addressed, with targeted approaches to overcome barriers to access Finally, the overall quality of lung cancer care must be improved, making multidisciplinary care available to all and ensuring survivorship is given due attention. Graphical abstract: Image 1 Highlights: Stigma remains a key issue for people with lung cancer, and needs urgent attention. Targeted screening through low-dose computed tomography must be implemented. Socioeconomic inequalities underpinning disparities in outcomes need to be tackled. Multidisciplinary care should be available to all.